Réponses

Meilleure réponse !
2014-10-26T14:38:05+01:00
35)
a) x - 1 = 1/6
6x/6 - 6/6 = 1/6
6/6x = 1/6 + 6/6
6x = 7
x = 7/6

b) 3x - 2 = 4/3
9/3x - 6/3 = 4/3
9/3x = 4/3 + 6/3
9x = 10
x = 10/9

c) 2/5x + 1 = 4/5
2/5x + 5/5 = 4/5
2/5x = 4/5 - 5/5
2x = - 1
x = - 1/2
x = - 0,5

d) 3/7x + 4 = - 8
3/7x + 28/7 = - 56/7
3x= - 56 - 28
3x = - 84
x = - 84/3
x = - 28

37)
a) 3 (x- 1) + 2 (x + 3) = 0
3x - 3 + 2x + 6 = 0
3x + 2x = 3 - 6
5x = - 3
x = - 3/5
x = - 0,6

b) - 5 (x + 2) + 3 (x - 3) = 7
- 5x - 10 + 3x - 9 = 7
- 5x + 3x = 7 + 10 + 9
- 2x = 26
x = - 26/2
x = - 13

c) 4 (- x + 1) - 2 (3x - 5) = 0
- 4x + 4 - 6x + 10 = 0
- 4x - 6x = - 10 - 4
10x = 14
x = 14/10
x = 1,4